Inventory, interpretation and assessment of the uraba basin’s free area geological, geochemical and geophysical information - Vargas-Cuervo, Germán; Castillo, Luis; Aguilera, Roberto; Jiménez, Diana María (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2010)
The Uraba Basin is located in the Northwest side of Colombia, in the Uraba Gulf. The basin is 3630 km2. It is composed of two physiographic environments: an offshore area located in the Uraba Gulf, which is 4150,45 km2 and a continental area divided in two subenvironments. The first one is formed by a plain morphology composed by fluviomarine plains and marshes which total surface is 3740 km2. The second environment is formed by a mountainous morphology composed of sedimentary and igneous rocks located to the Western and Eastern ends of the basin. The geophysical surface interpretation was based on seismic data (25 2D stack seismic lines) with TIFF images from scanned sections obtained from printed copies. This geophysical information includes the information obtained in one well drilled in the Uraba region: Apartado-1.  In order to determine the maturity and quality of the rock, a compilation of geochemical information was carried out. There are no reports of oil seeps, accumulations or hydrocarbon samples on the wells that would allow performing a crude analysis. There is not enough geochemical information that can be used to reliably determine the presence or no presence of source rocks in the area.